Isolated agenesis of the right pulmonary veins with pulmonary sequestration - Shilpa Patil; Sakshi Sachdeva; Shweta Bakhru; Bharat Dalvi; Nageswara Rao Koneti (Wolters Kluwer Medknow Publications, 2019)
We report two cases of agenesis of the right pulmonary veins (PVs) associated with sequestration of the right lung with systemic to pulmonary collateral. Both the children were referred for evaluation of recurrent lower respiratory tract infections. Transthoracic echocardiographic evaluation showed reversal of flow in the right pulmonary artery (PA) and absent right PVs. Cardiac catheterization confirmed the diagnosis of agenesis of the right PVs. Transcatheter closure of collaterals was performed in view of significant shunt from systemic to PA. Both the patients are asymptomatic on follow-up.